A boundary matter for a fifth-order private derivative differential equation with two double and one simple real characteristic - Sultanova Yulduzxon Kamoldinovna (Genius Journals, 2022)
The purpose of the study is to calculate the fifth order private derivative differential equation in a more convenient way.Theoretically poorly studied, these issues are able to be widely used in many issues in mechanics.
Keywords: Fifth Order; Private; Derivative; Real